SIMPLE EXPERIMENT OF DOPPLER EFFECT USING SMARTPHONE SENSOR - Malik, Adam; Mugiri, Widiastuti Ledgeriani; Zakwandi, Rizki; Safitri, Sani; Juliani, Tia (Jurnal Penelitian Fisika dan Aplikasinya (JPFA))
Doppler effect is physical phenomena which the emitted frequency is a source of change at a time when accepted by the detector due to relative movement of the detector towards the source of the wave or vice versa. In this research, conducted an activity measurement against Doppler effect symptoms by utilizing sensors found in smartphones. In this experiment, all mechanical instrument used is a smartphone with the help of software frequency sound generator, physics toolbox, the camera as an instrument of data collectors and software Tracker as motion analyzer. Based on the results of the experiment retrieved the value of the error and standard deviation of each of the observed symptoms. Symptoms affect Doppler upon source moving closer and away when the silent observer error value of 0.04% and% with a standard deviation of 0.1185 0.018 and 1.005. Experiment effect Doppler upon the source and observer approaching stationary gives error value of 8.60% and standard deviation 13.501 and to experiment the effect upon the source and Doppler observers moving each other approaching the error value of 4.31% and standard deviation of 0.087. Overall this experiment generates error value 3.267% and standard deviation of 3.665. So it could be inferred that the experiments conducted classified accurately and precision in effect phenomenon Doppler represents. Based on the results of this experiment the researcher recommends to carry out practical effects with the help of sensors Doppler smartphone.